2023
DOI: 10.1002/fsn3.3291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liposoluble components of highland barley spent grains on physiological indexes, intestinal microorganisms, and the liver transcriptome in mice fed a high‐fat diet

Abstract: The purpose of this study was to investigate the effects of the active ingredients of barley lees on the physiological indexes, intestinal flora, and liver transcriptome of mice fed a high‐fat diet. Twenty‐four male C57BL/6J mice were randomly divided into 4 groups and fed the experimental diets for 5 weeks. The results showed that the fat‐soluble components of distillers' grains significantly reduced body weight, abdominal fat, perirenal fat, blood glucose, low‐density lipoprotein cholesterol, triglycerides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Transcriptome analysis is emerging as a robust tool in the investigation of fundamental pathogenic mechanisms and discovery of therapeutic targets. It offers insights beyond phenotypic observations and provides valuable clues for further in‐depth studies (Perakakis et al., 2020 ; Zhang et al., 2023 ). In this study, we first confirmed the improvement effects of MHP against dyslipidemia and hepatic steatosis using a high‐fat high‐fructose (HFF) diet‐induced rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis is emerging as a robust tool in the investigation of fundamental pathogenic mechanisms and discovery of therapeutic targets. It offers insights beyond phenotypic observations and provides valuable clues for further in‐depth studies (Perakakis et al., 2020 ; Zhang et al., 2023 ). In this study, we first confirmed the improvement effects of MHP against dyslipidemia and hepatic steatosis using a high‐fat high‐fructose (HFF) diet‐induced rat model.…”
Section: Introductionmentioning
confidence: 99%